The English Nominal Group Structure with Special Reference to John Kerry and Ban Ki-moon’s Speech - Indah Suryadewi, Ni Kadek (Humanis; Vol 22 No 2 (2018)DO - 10.24843/JH.2018.v22.i02.p12, 2018)
This study entitled The English Nominal Group Structure with Special Reference to John Kerry and Ban Ki-Moon’s Speech is aimed to analyze the experiential structures and logical structure element s of nominal group used by John Kerry and Ban Ki-moon in their speech. The data were taken from the transcript of John Kerry and Ban Ki-moon’s speech at the United States Department of State in Washington, D.C. on February 14, 2013. Descriptive qualitative method was applied to analyze the experiential and logical structures of nominal group. The theory used to analyze it is the theory of Nominal Group proposed by Halliday and Matthiessen in the book entitled Halliday’s Introduction to Functional Grammar the fourth edition. The result of analysis shows that in the experiential structure, T structure becomes the most frequent structure that occurs followed by D+T and D+T+Q structure. Meanwhile, in the logical structure, H and M are the logical structure element s found. Therefore, from the structures found, John Kerry and Ban Ki-moon’s nominal group structures have a simple construction and it emphasizes Thing without adding any information .